Jelajah Ceria: Transformasi Strategi Bermain Sambil Belajar untuk Optimalisasi Tumbuh Kembang Anak Usia Dini - Mutmaina Djafar; Nunung Suryana Jamin (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2026)
Early childhood represents a critical foundational phase for cognitive, motor, and socio-emotional maturation. Traditional instructional models frequently encounter limitations in addressing individual developmental variances, thereby necessitating innovative, learner-centered pedagogical interventions. This community service initiative implemented the "Jelajah Ceria" (Cheerful Exploration) program, a structured play-based curriculum, at the Dulohupa Traditional House, Gorontalo. The intervention employed an experiential learning approach, facilitating a series of physical and cognitive activities including obstacle navigation, ball-handling drills, color-matching tasks, and exploratory play to stimulate holistic development. Field observations revealed diverse developmental responses among the participants. While a significant majority demonstrated enthusiastic engagement and tangible motor skill progression, a subset of participants required additional guided scaffolding to adapt to the learning environment. These findings underscore that targeted, play-centric interventions are effective in fostering meaningful learning experiences. The "Jelajah Ceria" model successfully bridges the gap between structured stimulation and organic learning, thereby providing a viable, replicable framework for enhancing early childhood holistic development within community-based educational settings.